Effect of Pollution on the Mechanical Properties of Clay Soil in Basrah (Garmatt Ali Zone), Iraq - Saeed, Nema Y.; A.Jasim, Nabeel; Ibrahim, Fatimah Khalil (Basrah Journal for Engineering Sciences, 2015)
The effect of pore fluid chemistry on the engineering properties of soil in Garmatt-Ali zone of Basrah was investigated. The tested soil is described as silty clay of low plasticity. The pore fluid was altered to include distilled water, raw sewage, and solutions of various salts such calcium carbonate, magnesium sulphate, and calcium chloride. Also, the solutions of salts were used with different concentration (0.25, 0.5, 0.75, 1.0 normality). The prepared samples of soil were tested after different exposure periods. The test program included determination of shear strength characteristics, consolidation characteristics, and Atterberg limits. The changes in shear strength, coefficient of permeability, void ratio – effective stress relationship, and Atterberg limits were recorded with the change in exposure period or the concentration of pore fluid solution. Generally, it was found that there are reductions in the shear strength of soil when the pore fluid is changed from distilled water to solutions of salts or raw sewage. Also it was found that there is a change in the calculated values of permeability, upon changing the type of pore fluid. The coefficient of consolidation for polluted soil was found to be less than that for the reference samples with distilled water.